Predictors of effective formal mentoring: Is the mentor's commitment all that matters?. Issue 3 (26th May 2016) - Rogers, Altovise; Luksyte, Aleksandra; Spitzmueller, Christiane
ABSTRACT: The present research explores how the intersection of motivation and ability contributes to mentoring success. Extending the motivation-aptitude model of performance to mentoring effectiveness and building on socioanalytic theory, we examined whether mentor commitment and other mentor attributes impacted supervisors' evaluation of mentors' effectiveness. Using self-report and third-party rating data from a sample of 102 mentors and 14 supervisors from a multinational organization, support was found for our hypotheses. Consistent with our theorizing about the importance of supplementing mentor commitment with important aptitudes, the results of the multilevel analyses showed that mentor commitment did not translate to mentoring effectiveness as rated by one's supervisor when mentors lacked getting along (i.e., self-monitoring and political skill) or getting ahead (learning goal orientation and strategic outlook) attributes.